Molecular epidemiology of drug-resistant Neisseria gonorrhoeae in Russia (Current Status, 2015). Issue 1 (December 2016) - Kubanov, Alexey; Vorobyev, Denis; Chestkov, Aleksandr; Leinsoo, Arvo; Shaskolskiy, Boris; Dementieva, Ekaterina; Solomka, Viktoria; Plakhova, Xenia; Gryadunov, Dmitry; Deryabin, Dmitriy
Abstract Background The widespread distribution ofNeisseria gonorrhoeae strains that are resistant to previously used and clinically implemented antibiotics is a significant global public health problem. In line with WHO standards, the national Gonococcal Antimicrobial Surveillance Programme (RU-GASP) has been in existence in Russia since 2004; herein, the current status (2015) is described, including associations betweenN. gonorrhoeae antimicrobial susceptibility, primary genetic resistance determinants and specific strain sequence types. Methods A total of 124 N. gonorrhoeae strains obtained from 9 regions in Russia in 2015 were examined usingN. gonorrhoeae Multi-Antigen Sequence Typing (NG-MAST), an antimicrobial susceptibility test according to European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria and an oligonucleotide microarray for the identification of mutations in thepenA, ponA, rpsJ, gyrA andparC genes responsible for penicillin G, tetracycline, and fluoroquinolone resistance. Genogroup (G) isolates were evaluated based on theirporB andtbpB sequence types (STs). Results NG-MAST analysis showed a diversified population ofN. gonorrhoeae in Russia with 58 sequence types, 35 of which were described for the first time. The STs 807, 1544, 1993, 5714, 9476 and 12531, which were typical for some Russian Federation regions and several countries of the former Soviet Union, were represented by five or more isolates. The internationally widespread ST 1407 was represented by a single strain in the present study. Division into genogroups facilitated an exploration of the associations betweenN. gonorrhoeae sequence type, antimicrobial resistance spectra and genetic resistance determinant contents. Preliminarily susceptible (G-807, G-12531) and resistant (G-5714, G-9476) genogroups were revealed. The variability in the most frequently observed STs and genogroups in each participating region indicated geographically restricted antimicrobial susceptibility inN. gonorrhoeae populations. Conclusions Resistance or intermediate susceptibility to previously recommended antimicrobials, such as penicillin G (60.5 %), ciprofloxacin (41.1 %) and tetracycline (25 %), is common in theN. gonorrhoeae population. Based on previous reports and current data, ceftriaxone and spectinomycin should be recommended for first-line empiric antimicrobial monotherapy for gonorrhoea in Russia.